Pengaruh Gaya Belajar dan Kemandirian Belajar terhadap Prestasi Belajar Matematika - Nurmalasary Nurmalasary (JKPM (Jurnal Kajian Pendidikan Matematika), 2018)
The purpose of this research was to know how far the influence of learning style, learning independence, learning styles and learning independence to mathematics learning achievement. The research method used is Expost Facto method. Based on the results of research by using the ANOVA two lines indicate that there are significant influences of learning style on mathematics learning achievement, there are not significant effects of learning independence on mathematics learning achievement and there is no interaction between learning styles and learning independence on mathematics learning achievement.